Optimum Splice Thickness Ratio Splicer of a Winding Machine to PE20KT Thread Splicing Quality - Hendri Pujianto; Bambang Yulianto; Hamdan S Bintang; Dinda Amelia Pramesti (Universitas Insan Cendekia Mandiri, 2023)
Winding machines are needed after the spinning process on ring-spinning machines because small packages of spinnerets are mostly not suitable for efficiently carrying out subsequent processes such as weaving and knitting. The splicer is independently actuated to optimize splicing cycles. PT Delta Dunia Tekstil II (DDT 2) is a company operating in the spinning industry, with the CD line producing 100% polyester yarn, which is used to make fabric in the knitting process. Based on observations, thread defects occur, such as loops and holes in the knitted fabric, because the thread splices resulting from the winding process are brittle and thin. Experiments on setting joint thickness parameters on splicer adjustment indicators 1–5 with a ratio of 0.25 were carried out. After carrying out the experiment, 3 ratios were obtained for sampling visual tests and joint strength, namely a ratio of 2.5, 2.75, and 3. Observing and calculating the splice strength of the three splicer ratios sampled, it was found that the ratio of parameter 3 in the splicer was visually very good and consistent. Strange results also meet the standard, of 92.37%. The optimal splicer ratio setting that can be used for the Carded 20 KT production process is setting the splicer ratio with a splice thickness parameter of 3.